Electron paramagnetic resonance and electric characterization of a [CH3NH2NH2][Zn(HCOO)3] perovskite metal formate framework. Issue 18 (24th April 2017) - Šimėnas, Mantas; Balčiūnas, Sergejus; Trzebiatowska, Monika; Ptak, Maciej; Mączka, Mirosław; Völkel, Georg; Pöppl, Andreas; Banys, Jūras
Abstract : We present an EPR and electric characterization study of structural phase transitions in a novel methylhydrazinium formate framework. Abstract : We present a combined continuous-wave (CW) and pulse electron paramagnetic resonance (EPR), pulse electron-nuclear double resonance (ENDOR), pyrocurrent as well as broadband dielectric study of a [CH3 NH2 NH2 ][Zn(HCOO)3 ] dense perovskite metal–organic framework (MOF). The pyroelectric current of a single crystal sample reveals two structural phase transitions at T c1 = 325 and T c2 = 173 K that are related to the ordering of CH3 NH2 NH2 + cations. The dielectric permittivity exhibits a small kink at T c1 implying improper ferroelectric phase transition, while much stronger anomaly is observed at T c2 . The dielectric spectra of the intermediate phase reveal a Cole–Cole relaxation process that is assigned to the hopping motion of the CH3 NH2 NH2 + cations. EPR and ENDOR experiments are performed on powder MOF samples doped with small amounts of paramagnetic Mn 2+ and Cu 2+ probe ions. CW EPR spectra reveal the successful incorporation of these ions at the Zn 2+ lattice sites, while ENDOR measurements indicate several proton species that are in excellent agreement with the X-ray diffraction data. The CW EPR linewidth and intensity of the Mn 2+ spectra demonstrate anomalies at the phase transition points. The direct measurements of the phase memory time T m of the Mn 2+ centers indicate a second motional process of CH3 NH2 NH2 + cations below T c2 . The measurements of the longitudinal relaxation time T 1 of the low-temperature phase reveal a coupling between the electron spins and a hard optical phonon mode which undergoes a damping due to the coupling with the relaxational mode as T c2 is approached. The temperature dependent Mn 2+ and Cu 2+ spectra reflect the structural changes of the metal–oxygen octahedra. The fine structure splitting of Mn 2+ ions is increasing as the temperature is decreased reflecting a distortion of the MnO6 octahedra. The Cu 2+ hyperfine interaction demonstrates a first-order character close to the tricritical limit of the phase transition at T c2 .